Radiative equilibrium temperature of the atmosphere along 80oE longitude (MAUSAM, 1970)
Radiative equilibrium temperature has been computed .as the asymptotic steady state of an initial value problem by marching process. The sigma-coordinate system has been used in which the earth's surface is one of the coordinate surfaces. The effects of long wave radiation due; to water vapour, carbon dioxide, and ozone and of absorption of solar radiation by these gases have been take Into account. Also, the effects of reflected solar energy by clouds have been considered and the scheme developed In this regard has been described. The heat balance condition at the earth's surface has been used to predict the surface temperature. The effect of convection has been included such that the computed lapse rate is adjusted to dry adiabatic lapse rate whenever the lapse rate exceeds the dry adiabatic lapse rate. The results show that ozone is mainly responsible for maintaining warm stratosphere and that in the stratosphere the conditioll8 of radiative equilibrium are satisfied. In the troposphere, there 18 a net radiative cooling. The equilibrium solution also reveals tropopause height variation with latitude.